<> modelling study of atmospheric cycle of mercury and its exchange processes at environmental interfaces - De Simone, Francesco; Bertolini, Roberto; Carbone, Vincenzo; Pirrone, Nicola; HedgecocK, Ian M. (My University, 2015)
Since ancient times human activities have significantly altered the natural global Mercury (Hg) cycle through emissions to the environment. Hg is a global pollutant since its predominant atmospheric form, elemental Hg, reacts relatively slowly with the more abundant atmospheric oxidants and is therefore transported long distances from its emission source. Once oxidised however Hg is readily deposited, an can then be converted to the toxic monomethylmercury (MeHg) in soils and natural waters. MeHg is able to bioaccumulate and biomagnify, up to levels at which it is harmful to human health. Mercury pollution is therefore a threat to ecosystem health on a global scale, and is now being addressed by an international agreement, the Minamata Convention. Comprehensive knowledge of the details of the atmospheric Hg cycle is still lacking, and in particular there is some uncertainty regarding the atmospherically relevant reduction-oxidation reactions of mercury and its compounds. The exchange of Hg and its compounds between the atmosphere and the oceans also plays an important role in the cycling of mercury in the environment: understanding and quantifying mercury deposition patterns and fluxes is critically important for the assessment of the present, and future, environmental impact of mercury contamination. ECHMERIT is a global on-line chemical transport model, based on the ECHAM5 global circulation model, with a highly customisable chemistry mechanism designed to facilitate the investigation of both aqueous and gas phase atmospheric mercury chemistry. An improved version of the model which includes a new set of emissions routines, both on-line and off-line, has been developed and used for this thesis to investigate and assess a number of the uncertainties related to the Hg atmospheric cycle. Outputs of multi-year model simulations have been used to validate the model and to estimate emissions from oceans. Various redox mechanisms have been included to assess how chemical reactions influence the models ability to reproduce measured Hg concentrations and deposition flux patterns. To characterize the Hg emissions which result from Biomass Burning , three recent biomass burning inventories (FINNv1.0, GFEDv3.1 and GFASv1.0) were included in the model and used to investigate the annual variation of Hg. The differences in the geographical distribution and magnitude of the resulting Hg deposition fluxes, hence the uncertainty associated with this Hg source, were quantified. The roles of the Hg/CO enhancement ratio, the emission plume injection height, the Hg0 (g) oxidation mechanism and lifetime, and the inventory chosen, as well as their uncertainty were considered. The greatest uncertainties in the total deposition of Hg due to fires were found to be associated with the Hg/CO enhancement ratio and the emission inventory employed. Deposition flux distributions proved to be more sensitive to the emission inventory and the oxidation mechanism chosen, than all the other model parameters. Over 75% of Hg emitted from biomass burning is deposited to the world’s oceans, with the highest fluxes predicted in the North Atlantic and the highest total deposition in the North Pacific. The net effect of biomass burning is to liberate Hg from lower latitudes and disperse it towards higher latitudes where it is eventually deposited. Finally, the model was used to evaluate the fate of the Hg released into the atmosphere by human activities. Anthropogenic emissions are estimated to amount to roughly 2000Mg/y (1000-4000 Mg/y). Hg speciation (elemental, oxidised or associated with particulate matter) is subject to many uncertainties: the extremely variable lifetimes among Hg species, as well as the Hg emission heights, in combination with the complex physical and chemical mechanisms that drive its final fall-out lead to considerable uncertainties. To address this specific issue three anthropogenic Hg emission inventories, namely AMAP-UNEP, EDGAR and Streets, were included in the Model. Different model parametrisations were adopted to trace the fate of Hg to its final receptors and to thoroughly test the model performance against the measurements. Primary anthropogenic Hg contributes up to 40% of the present day Hg deposition. The oxidation mechanism has a significant impact on the geographical distribution of the deposition of Hg emitted from human activities globally, : 63% is deposited to the world’s oceans. The results presented in this thesis provide a new and unique picture of the global cycle of mercury, evaluating and assessing the uncertainties related to many aspects with an on-line Global Circulation Model developed specifically to investigate the global atmospheric Hg cycle.
Scuola di Dottorato Scienza e Tecnica "Bernardino Telesio", Fisica dei Sistemi Complessi, XXVIII Ciclo, a.a. 2015-2016
Keywords: Pollution; Mercury